Telegram (translation) - Jouhaux, Léon, 1879-1954
1939-01-28 012b-0057-002 TRANSLATION TEXT OF TELEGRAM SENT TO: DALADIER CHAMBERLAIN ROOSEVELT. For the safeguarding of Peace, the defence of democracy and liberty, in the name of the right of nations to self-determination, we urge you to take without delay all necessary steps to secure an early meeting of the three great democracies ) U.S.A., Great Britain and France - in order that decisions may be made on the measures to be taken to avert the perils which threaten humanity, and to give Republican Spain, in respect for international law, the means of defence against her rebel elements and the foreign invasion which, if it were to prove victorious, would risk dragging us into war. The C.G.T., expressing the conviction of the French working class, and translating that of the workers of all other free countries, assures you of its fullest support in this joint action by the democracies. For the C.G.T. (signed) Léon Jouhaux, General Secretary. AC. 292/946/12b/58